Make Your Tools Sparkle with Trust: The PICSE Framework for Trust in Software Tools - Johnson, Brittany; Bird, Christian; Ford, Denae; Forsgren, Nicole; Zimmermann, Tom (ICSE SEIP, 2023)
The day to day of a software engineer involves a variety of tasks. While many of these tasks are collaborative and completed as such, it is not always possible or feasible to engage with other engineers for task completion. Software tools, such as code generators and static analysis tools, aim to fill this gap by providing additional support for developers to effectively complete their tasks. With a steady stream of new tools that emerging to support software engineers, including a new breed of tools that rely on artificial intelligence, there are important questions we should aim to answer regarding the trust engineers can, and should, put into their software tools and what it means to build a trustworthy tool. In this paper, we present findings from an industry interview study conducted with 18 engineers across and external to the Microsoft organization. Based on these interviews, we introduce the PICSE (pronounced "pixie") framework for trust in software tools to provide preliminary insights into factors that influence engineer trust in their software tools. We also discuss how the PICSE framework can be considered and applied in practice for designing and developing trustworthy software tools.